Altered white matter microstructure underlies listening difficulties in children suspected of auditory processing disorders: a DTI study - Farah, Rola (Blackwell Publishing Ltd, 2014)
INTRODUCTION: The purpose of the present study was to identify biomarkers of listening difficulties by investigating white matter microstructure in children suspected of auditory processing disorder (APD) using diffusion tensor imaging (DTI). Behavioral studies have suggested that impaired cognitive and/or attention abilities rather than a pure sensory processing deficit underlie listening difficulties and auditory processing disorder (APD) in children. However, the neural signature of listening difficulties has not been investigated. METHODS: Twelve children with listening difficulties and atypical left ear advantage (LEA) in dichotic listening and twelve age- and gender-matched typically developing children with typical right ear advantage (REA) were tested. Using voxel-based analysis, fractional anisotropy (FA), and mean, axial and radial diffusivity (MD, AD, RD) maps were computed and contrasted between the groups. RESULTS: Listening difficulties were associated with altered white matter microstructure, reflected by decreased FA in frontal multifocal white matter regions centered in prefrontal cortex bilaterally and left anterior cingulate. Increased RD and decreased AD accounted for the decreased FA, suggesting delayed myelination in frontal white matter tracts and disrupted fiber organization in the LEA group. Furthermore, listening difficulties were associated with increased MD (with increase in both RD and AD) in the posterior limb of the internal capsule (sublenticular part) at the auditory radiations where auditory input is transmitted between the thalamus and the auditory cortex. CONCLUSIONS: Our results provide direct evidence that listening difficulties in children are associated with altered white matter microstructure and that both sensory and supramodal deficits underlie the differences between the groups.